Computer simulation of position and maximum of linear polarization of asteroids. (January 2018) - Petrov, Dmitry; Kiselev, Nikolai
Highlights: The ground-based observations of near-Earth asteroids were carried out. The position of polarization maximum depends on asteroid's albedo. The computer simulations of the polarimetrical properties of asteroids were done. The influence of the refractive indices on the linear polarization maximum is studied. Abstract: The ground-based observations of near-Earth asteroids at large phase angles have shownsome feature: the linear polarization maximum position of the high-albedo E-type asteroids shifted markedly towards smaller phase angles (αmax ≈ 70°) with respect to that for the moderate-albedo S-type asteroids (αmax ≈ 110°), weakly depending on the wavelength.To study this phenomenon, the theoretical approach and the modified T-matrix method (the so-called Sh-matrices method) were used. Theoretical approach was devoted to finding the values of αmax, corresponding to maximal values of positive polarization P max . Computer simulations were performed for an ensemble of random Gaussian particles, whose scattering properties were averaged over with different particle orientations andsize parameters in the range X = 2.0 ... 21.0, with the power law distribution X − k, where k = 3.6. The real parts of the refractive index mr were 1.5, 1.6 and 1.7. Imaginary part of refractive index varied from m i = 0.0 to mi = 0.5. Both theoretical approach and computer simulation showed that the value of αmax strongly depends on the refractive index. The increase of mi leads to increased αmax and P max . In addition, computer simulation shows that the increase of the real part of the refractive index reduces P max .Whereas E-type high-albedo asteroids have smaller values of m i, than S -type asteroids, we can conclude, that value of αmax of E-type asteroids should be smaller than for S –type ones. This is in qualitative agreement with the observed effect in asteroids.